Technological Pedagogical Content Knowledge (TPACK) and Suitability of Educational Technology (EdTech) on Teaching and Learning Among Chinese Language Teachers in China - Li Xia, Wang (Universiti Malaysia Sarawak, 2026)
China’s rapid digital transformation in education,supported by initiatives such as the Smart Education of China (SEC) platform and AI-driven reforms, has accelerated the integration of Educational Technology (EdTech) into classroom teaching. For Chinese language (CL) education, however, successful adoption depends not only on access to tools but also on teachers’ ability to integrate them meaningfully through Technological Pedagogical Content Knowledge (TPACK). This study investigated the relationship between TPACK, EdTech suitability, and teacher readiness among in-service CL teachers in China. A quantitative, cross-sectional survey was conducted using validated instruments to measure six TPACK components, four EdTech suitability dimensions (Educational Effectiveness, Content Fidelity, Feedback, Professional Development), and three readiness factors (Confidence, Digital Skills, Perceived Barriers). Data were analyzed using ANOVA, correlation, regression, and structural equation modeling (SEM).Findings revealed consistently high perceptions of EdTech suitability across demographic groups, with no significant differences by age, experience, or education level. Strong correlations were found between TPACK and both Educational Effectiveness and Content Fidelity, while Feedback showed moderate correlations and Professional Development only weak associations. Regression results confirmed that TPACK predicted 45–55% of variance in EdTech suitability. Moreover, EdTech suitability significantly predicted teacher readiness, indicating that when tools are perceived as effective and content-accurate, teachers report higher confidence and stronger digital skills, with fewer barriers. The study extends the TPACK framework by explicitly linking teacher competence with EdTech suitability and readiness, offering theoretical, practical, and policy insights for advancing meaningful technology integration in CL education.